2018
DOI: 10.1177/0963662518799564
|View full text |Cite
|
Sign up to set email alerts
|

Framing genetically modified mosquitoes in the online news and Twitter: Intermedia frame setting in the issue-attention cycle

Abstract: We investigate how the online news and Twitter framed the discussion about genetically modified mosquitoes, and the interplay between the two media platforms. The study is grounded in the theoretical frameworks of intermedia agenda setting, framing, and the issue-attention cycle and combines methods of manual and computational content analysis, and time series analysis. The findings show that the Twitter discussion was more benefit-oriented, while the news coverage was more balanced. Initially, Twitter played … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 36 publications
(49 reference statements)
0
23
0
1
Order By: Relevance
“…For example, our current research examines Twitter messages about genome editing, including how these messages are framed, the main concepts and themes within them, and the sentiment of the messages. In addition, it will be important to examine the effects of the reporting of significant events related to genome editing on Twitter and the news, similar to W. Wang and Guo’s (2018) study on the intermedia framing effects of genetically modified mosquitoes during the outbreak of the Zika virus.…”
Section: Discussionmentioning
confidence: 99%
“…For example, our current research examines Twitter messages about genome editing, including how these messages are framed, the main concepts and themes within them, and the sentiment of the messages. In addition, it will be important to examine the effects of the reporting of significant events related to genome editing on Twitter and the news, similar to W. Wang and Guo’s (2018) study on the intermedia framing effects of genetically modified mosquitoes during the outbreak of the Zika virus.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies focusing on social media in connection with science-related topics have explored communicative networks in relation to various scientific issues [Büchi, 2017], and how various stakeholders make use of social media, for instance, government organizations [Dalrymple, Young and Tully, 2016], academics [Mewburn and Thomson, 2013], and environmental movements [Hestres, 2014;Hutchins, 2016]. Studies have concentrated heavily on the platform Twitter, examples being the role of Twitter in shaping the climate debate [Auer, Zhang and Lee, 2014;Kirilenko and Stepchenkova, 2014], creating open forums as well as echo chambers for climate discussion [Williams et al, 2015], framing IPCC assessment reports [O'Neill et al, 2015], issues pertaining to genetic modification [Wang and Guo, 2018] and nanotechnology [Veltri, 2012]. To a large extent, however, Twitter is associated with elite discourse, and a recent study [Hargittai, Füchslin and Schäfer, 2018], identified Facebook as significantly more attractive for non-specialists when engaging with scientific issues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social media has also been employed in health interventions such as preventing smoking [16] and may be harnessed to improve awareness of foodborne illness [17]. Investigations comparing online news to Twitter about genetically modified (GM) mosquitoes revealed that Twitter discussion was more benefitoriented whilst news media was more balanced [18]. Although not all the information being posted on social media outlets was accurate, there were significantly more evidence-based and informative posts than not [19].…”
Section: Introductionmentioning
confidence: 99%